‘Ajami as painted wooden wall panelling for living spaces of interior design from two master atisants perspective - Baydoun, Ziad; Kamaruddin, Zumahiran (WMT Group Sdn. Bhd., 2017)
Ajami handmade art as wood paneling has been popularly practiced in the sixteenth to late eighteenth century especially during Omayyad and the Ottoman period. ‘Ajami is used to describe the technique of painted wooden wall panel as well as the interior as a whole. Nowadays, it can be seen that this beautiful decorative painting technique is subjected to threats and would gradually become one of an extinct art in Syria. This paper discusses the rediscovering of traditional techniques of ‘Ajami and its visual attributes in the painted wood paneling products of two Syrian master artisans who are actively involved in the craft industry, namely Abdulraouf Baydoun and Fadi raeed. Their works and opinions were obtained through face-to-face interviews that served as inferential evidences and primary data for this study. The interviews focused on the aspect of fabrication and innovation of ‘Ajami as painted wood paneling with particular emphasis on visual components and techniques used. Field observation and photographic documentation of their works were necessary measures to complement the interviews. Hence, examination on the works produced by the artisans which exemplifies their distinctive craftsmanship is also addressed in this paper. It was found that the most profound works produced by them are ‘Ajami for interior application with distinctive techniques and visual attributes. The finding also signifies their strong preferences to the application of floral and geometrical design for innovative wood paneling. This implies that the development of new ideas based on the traditional techniques has become the most influencing factor that governs their craftsmanship in sustaining the applied art and design of ‘Ajami in Syria.